IMPLEMENTING PROPHETIC VALUES IN THE ISLAMIC LIFE GUIDELINES FOR MUHAMMADIYAH CITIZENS: A Qualitative Analysis for Transforming Science and Technology - Qorib, Muhammad; Afandi, Ahmad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
Rapid advances in science and technology have significantly changed various aspects of human life, so a humane and sustainable approach is needed in its development. This article aims to explore and analyze how the prophetic values contained in the Muhammadiyah Islamic Life Guidelines can guide the transformation of science and technology. Using a qualitative approach and desk research, this article analyzes key prophetic values such as tolerance, togetherness, brotherhood, and social care. The results show that these values provide a strong ethical and spiritual framework for the responsible and sustainable application of science and technology. The integration of these prophetic values in the development of science and technology can encourage more inclusive and harmonious progress, thus providing extensive benefits to society and the environment. Thus, this article emphasizes the importance of a holistic approach that incorporates prophetic values in dealing with the transformation of science and technology. Keywords: Prophetic Values, Muhammadiyah Life Guidelines, Transformation of Science and Technology.